Electrical profile of ultra violet (UV) curable renewable polymer graphite (PG) composites - Nur Munirah Abdullah; A. Z. M. Rus; M. F. L. Abdullah; Hanani Abd Wahab (Institute of Advanced Engineering and Science, 2020)
The electrical profiles of the renewable polymer graphite (PG) composites upon ultra violet (UV) curing were investigated. Renewable PG films were prepared by mixing with varying weight percent of graphite (with an increment of 5 wt. % of prepared graphite) up to 30 wt.% and crosslinker. Then, the composites solution was slip casted and cured upon stimulated UV irradiation (UV accelerated weathering tester) at different time exposure (up to 1000 hours) was applied. Small changes on the functional groups of the composites were observed due to UV exposure time by Fourier Transform Infrared Spectroscopy (FTIR). Suggesting that chemical crosslink and chain scissions occurred within renewable polymer graphite composites. Further electrical profile through two point probe and four point probe method recorded visibly fluctuating values for both resistivity and conductivity within its composites range. Proposed here that the removal of organic contaminants and weak materials form both renewable polymer and graphite particles through the UV curing may have an effect on the formation of conductive network stability.